Effects of non-phthalate plasticizer bis(2-ethylhexyl) sebacate (DEHS) on the endocrine system in Japanese medaka (Oryzias latipes) - Horie, Yoshifumi; Nomura, Miho; Ramaswamy, Babu Rajendran; Harino, Hiroya; Yap, Chee Kong; Okamura, Hideo (Elsevier, 2023)
Water pollution due to plasticizers is one of the most severe environmental problems worldwide. Phthalate plasticizers can act as endocrine disruptors in vertebrates. In this study, we investigated whether the non-phthalate bis(2-ethylhexyl) sebacate (DEHS) plasticizer can act as an endocrine disruptor by evaluating changes in the expression levels of thyroid hormone-related, reproduction-related, and estrogen-responsive genes of Japanese medaka (Oryzias latipes) exposed to the plasticizer. Following the exposure, the gene expression levels of thyroid-stimulating hormone subunit beta (tshβ), deiodinase 1 (dio1), and thyroid hormone receptor alpha (trα) did not change. Meanwhile, DEHS suppressed dio2 expression, did not induce swim bladder inflation, and eventually reduced the swimming performance of Japanese medaka. These findings indicate that DEHS can potentially disrupt the thyroid hormone-related gene expression and metabolism of these fish. However, exposure to DEHS did not induce changes in the gene expression levels of kisspeptin 1 (kiss1), gonadotropin-releasing hormone (gnrh), follicle-stimulating hormone beta (fshβ), luteinizing hormone beta (lhβ), choriogenin H (chgH), and vitellogenin (vtg) in a dose-dependent manner. This is the first report providing evidence that DEHS can disrupt thyroid hormone-related metabolism in fish.